The Motive of Service As a Determinant of the Psychological Stability of the Medical Worker: Statement of the Problem - Barykina, A; Shutova, N (KnE Life Sciences, 2018)
The professional activity of emergency medical service workers is of critical significance, as it aims to preserve, support, and develop the health of individuals and society, in the face of considerable intellectual, emotional, and physical tension. One of the most important qualities that safeguards the mental health of emergency medical service workers is the psychological stability of the individuals under working conditions. The objective of this study was to explore the psychological content of the motive of service as a determinant of the psychological stability of the emergency medical service worker. Our results show that the desire to help, to serve people, which we call ‘the motive of service’, relates to higher motives. The motive of service as a psychological category has not been explored, neither in domestic nor international psychological science. The motive of service as a manifestation of an individual’s altruistic orientation gives a moral vector to professional behavior and is a system-shaping element in the motivational component of the psychological stability of the medical worker. Keywords: motive of service, psychological stability, medical worker